2020
DOI: 10.3390/mi11111007
|View full text |Cite
|
Sign up to set email alerts
|

DoE Analysis of Approaches for Hydrogel Microbeads’ Preparation by Millifluidic Methods

Abstract: Hydrogel microbeads hold great promise for immune-protective cell transplants and in vitro studies. Millifluidic generation of hydrogel microbeads is a highly efficient and reproducible approach enabling a mass production. This paper illustrates the preparation and characterization of highly controlled and reproducible microbeads made by different types of hydrogel using millifluidic approaches. The optimization of the process was made by a design of experiments (DoE) approach. The microbeads’ large-scale prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In an atomization process, Chan et al [ 49 ] also found that an increase in volumetric liquid flow rate (equivalent to pump flow in this work) also produced larger particles. Similar effects of the air flow in microparticle’s diameter were also observed in previous works, with higher air flows decreasing the size [ 20 , 50 ]. Nastruzzi et al [ 50 ] also found that height (equivalent to bath-nozzle gap) and flow (equivalent to pump flow) also did not significantly affect the particle’s size.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In an atomization process, Chan et al [ 49 ] also found that an increase in volumetric liquid flow rate (equivalent to pump flow in this work) also produced larger particles. Similar effects of the air flow in microparticle’s diameter were also observed in previous works, with higher air flows decreasing the size [ 20 , 50 ]. Nastruzzi et al [ 50 ] also found that height (equivalent to bath-nozzle gap) and flow (equivalent to pump flow) also did not significantly affect the particle’s size.…”
Section: Discussionsupporting
confidence: 85%
“…Similar effects of the air flow in microparticle’s diameter were also observed in previous works, with higher air flows decreasing the size [ 20 , 50 ]. Nastruzzi et al [ 50 ] also found that height (equivalent to bath-nozzle gap) and flow (equivalent to pump flow) also did not significantly affect the particle’s size. The use of needles with different diameters should also be studied in future works, since the needle affects the shear rate [ 31 ].…”
Section: Discussionsupporting
confidence: 85%
“…We and others have used DoE to predict responses of hydrogels and cells within hydrogels in systems with multiple input variables. 8,[11][12][13][14] This approach can be widely used in regenerative medicine applications such as scaffold design, cell culture optimization, and the development of in vitro model systems, accelerating the timeframe in which new platforms can be optimized. [15][16][17] In this study, we were specifically interested in tuning the properties of hyaluronic acid hydrogels formed via hydrazone crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have used DoE to predict responses of hydrogels and cells within ed f he of hydrogels in systems with multiple input variables. (8,(11)(12)(13)(14) This approach can be widely used in regenerative medicine applications such as scaffold design, cell culture optimization, and the development of in vitro model systems, accelerating the timeframe in which new platforms can be optimized. (15)(16)(17) In this study, we were specifically interested in tuning the properties of hyaluronic acid hydrogels formed via hydrazone crosslinking.…”
Section: Introductionmentioning
confidence: 99%